FABRICATION AND PERFORMANCE EVALUATION OF ZEOLITE RHO/POLYSULFONE AND AMINE-MODIFIED ZEOLITE RHO/POLYSULFONE MIXED MATRIX MEMBRANES IN CO2/CH4 SEPARATION - YIT SIEW, TIFFANY NG (2020)
Over the past few years, mixed matrix membranes (MMMs) have received worldwide attention in gas separation industry. It stems from the fact that MMMs are highly potential in CO2 and CH4 gas permeation application. In reference to different inorganic fillers, zeolites with well-defined, uniform pore channels and molecular sieving properties are able to provide high gas separation performance compared to polymeric membranes. However, the incorporation of zeolite into MMMs has usually led to the formation of undesirable interfacial voids and filler agglomeration which may jeopardize the gas permeation performance of the MMMs. In current work, zeolite RHO and amine-modified zeolite RHO (NH2-RHO) were separately incorporated into polysulfone (PSf) to form MMMs.